Rate of Metabolic Syndrome Among Patients with Facial Acanthosis Nigricans (Bangladesh Medical Journal, 2019)
Facial acanthosis nigricans (FAN) is an ignored dermatological entity. Nowadays it occurs more frequently than previous days may be due to changing economic and social status of our country. Aim of this study was to assess the rate of metabolic syndrome in cases of facial acanthosis nigricans. This observational study was conducted in the outpatient department (OPD) of dermatology and Venereology of Bangabandhu Sheikh Mujib Medical University (BSMMU) in the year 2017 among thirty clinically diagnosed cases of FAN. After taking their informed written consent; BMI, random plasma glucose, fasting lipid profile and serum insulin level was estimated in venous blood and recorded accordingly. To confirm metabolic syndrome we followed NCEP ATP III guideline (2005) where 3 of 5 positive criteria confirmed the diagnosis. All data was preserved in a secured computer device and was analyzed with SPSS program with appropriate statistical tools. Mean (±SD) age of patients was 35.63 ± 14.26 years and male to female ratio was 1:1.14. The mean BMI of cases was 33.73±3. We found 11 cases with hypertension, 8 with type II diabetes mellitus and 9 with dyslipidemia. Among the 30 cases of FAN 12 zygomatic type, 8 generalized type and 5 had band like pigmentation on the forehead. Twenty-three patients had acanthosis nigricans on both sides of body. According to our preset criteria we found 26.66% cases had metabolic syndrome. The rate of metabolic syndrome is higher in facial acanthosis nigricans patients. A further large scale study is recommended for strengthening this study findings.Bangladesh Med J. 2018 May; 47 (2): 12-16